Backward Glances : Contemporary Chinese Cultures and the Female Homoerotic Imaginary - Martin, Fran, 1971- (Book collections on Project MUSE., 2010)
Examining a broad range of media (texts, film, television soap operas, comics, pop music, internet) this book studies lesbian representation in the contemporary Chinese mass cultures that circulate between the PRC, Taiwan and Hong Kong.